THE PROBLEM OF HUMAN RIGHTS AND TOLERANCE IN UZBEKISTAN (World Bulletin of Management and Law, 2023)
This article discusses the challenges of human rights and tolerance in Uzbekistan, highlighting the historical context and current issues faced by the country. It explores the restrictions on freedom of expression, lack of judicial independence, and the need to promote tolerance and inclusivity among diverse ethnic and religious groups. The article recognizes the positive steps taken by the Uzbek government while emphasizing the importance of continued progress. It suggests strengthening the rule of law, empowering civil society, and implementing educational reforms to foster a more inclusive and tolerant society.